Vaginal microbiota dysmicrobism and role of biofilm-forming bacteria. - Campisciano, Giuseppina; Zanotta, Nunzia; Petix, Vincenzo; Corich, Lucia; De Seta, Francesco; Comar, Manola (Front Biosci (Elite Ed), 2018)
Bacterial vaginosis involves the presence of a polymicrobial biofilm on the vaginal epithelium, guaranteeing immune escape and spread of antibiotic resistance. To spot known biofilm-forming bacteria, we profiled the vaginal microbiome of sixty-four symptomatic women suffering from a different grade of vaginal disorders and sixty asymptomatic healthy women. Specific microbial profiles distinguished symptomatic from asymptomatic women and characterized the grade of dysmicrobism within the symptomatic group. Lactobacillus crispatus and iners predominated on the healthy vaginal mucosa, while Lactobacillus gasseri predominated in the intermediate dysmicrobism. Furthermore, the intermediate grade of dysmicrobism was characterized by other lactic acid-producers species than Lactobacilli, able to rescue the microbial imbalance, and Ureaplasma parvum-serovar 3. The vaginosis group exhibited the overgrowth of Prevotella bivia, which is known to enhance the biofilm formation by Gardnerella vaginalis, and the presence of Streptococcus anginosus, which is emerging as a new cooperating player of the vaginal biofilm. Identifying specific microorganisms promoting or preventing the biofilm formation could increase the accuracy for a better definition of the vaginal dysmicrobism concept and therapeutic intervention.
Keywords: Adult; Biofilms; Female; Humans; Microbiota; Vagina; Vaginosis, Bacterial